Inside Back Cover: Toward Arbitrary Control of Lattice Interactions in Nonequilibrium Condensates (Adv. Quantum Technol. 2/2020). Issue 2 (13th February 2020) - Kalinin, Kirill P.; Berloff, Natalia G.
Abstract : There is a growing interest in investigating new states of matter using out‐of‐equilibrium lattice spin models in two dimensions. However, a control of pairwise interactions in such systems has been elusive as due to their nonequilibrium nature they maintain nontrivial particle fluxes even at the steady state. In article number 1900065 Natalia Berloff and co‐workers suggest how to overcome this problem and formulate a method for engineering reconfigurable networks of nonequilibrium condensates with control of individual pairwise interactions.